2021
DOI: 10.1186/s40168-021-01126-6
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic and docosahexaenoic acids attenuate hyperglycemia through the microbiome-gut-organs axis in db/db mice

Abstract: Background Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have been suggested to prevent the development of metabolic disorders. However, their individual role in treating hyperglycemia and the mechanism of action regarding gut microbiome and metabolome in the context of diabetes remain unclear. Results Supplementation of DHA and EPA attenuated hyperglycemia and insulin resistance without changing body weight in db/db mice while the ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 91 publications
2
78
0
Order By: Relevance
“…Previous studies showed that bile acids, SCFAs, and glutathione were involved in hepatocyte apoptosis. 34 , 39 , 40 The present study performed a metabonomic analysis of SCFAs and bile acids in the livers of Van- and Gen-treated mice (Supplementary Figures S7, S8). The levels of some SCFAs and bile acids in the livers of the Gen-treated mice were significantly higher than the Van-treated mice (Supplementary Figures S7c and S8).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that bile acids, SCFAs, and glutathione were involved in hepatocyte apoptosis. 34 , 39 , 40 The present study performed a metabonomic analysis of SCFAs and bile acids in the livers of Van- and Gen-treated mice (Supplementary Figures S7, S8). The levels of some SCFAs and bile acids in the livers of the Gen-treated mice were significantly higher than the Van-treated mice (Supplementary Figures S7c and S8).…”
Section: Resultsmentioning
confidence: 99%
“…The normal control group was given a normal chow diet (AIN-93 diet), while rats of the model control group were given a high fat diet (HFD) for 8 weeks (Table 1). 22–25 Then, the rats of the model control group were overnight fasted, weighed, and injected intraperitoneally with STZ at 35 mg kg −1 . The rats of the normal control group received only the same volume of citrate buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Primary and secondary bile acids can stimulate the farnesoid X receptor and GPCR-19 to regulate glucose metabolism. 41 Conjugated primary bile acids (glucocholic acid, taurine, etc.) were positively associated with T2DM risk, 42 which is consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%